Commentary: Ethical Issues of Current Health-Protection Policies on Low-Dose Ionizing Radiation. Issue 2 (1st April 2014) - Socol, Yehoshua; Dobrzyński, Ludwik; Doss, Mohan; Ludwig E., Feinendegen; Janiak, Marek K.; Miller, Mark L.; Sanders, Charles L.; Scott, Bobby R.; Ulsh, Brant; Vaiserman, Alexander
The linear no-threshold (LNT) model of ionizing-radiation-induced cancer is based on the assumption that every radiation dose increment constitutes increased cancer risk for humans. The risk is hypothesized to increase linearly as the total dose increases. While this model is the basis for radiation safety regulations, its scientific validity has been questioned and debated for many decades. The recent memorandum of the International Commission on Radiological Protection admits that the LNT-model predictions at low doses are "speculative, unproven, undetectable and 'phantom'." Moreover, numerous experimental, ecological, and epidemiological studies show that low doses of sparsely-ionizing or sparsely-ionizing plus highly-ionizing radiation may be beneficial to human health (hormesis/adaptive response). The present LNT-model-based regulations impose excessive costs on the society. For example, the median-cost medical program is 5000 times more cost-efficient in saving lives than controlling radiation emissions. There are also lives lost: e.g., following Fukushima accident, more than 1000 disaster-related yet non-radiogenic premature deaths were officially registered among the population evacuated due to radiation concerns. Additional negative impacts of LNT-model-inspired radiophobia include: refusal of some patients to undergo potentially life-saving medical imaging; discouragement of the study of low-dose radiation therapies; motivation for radiological terrorism and promotion of nuclear proliferation.